1985
DOI: 10.1071/mf9850773
|View full text |Cite
|
Sign up to set email alerts
|

Mating and spawning in the mudcrab, Scylla serrata (Forskaål) (Decapoda: Portunidae), in Moreton Bay, Queensland

Abstract: Mating activity in a southern Queensland population of S. serrata was at a maximum level in mid-spring and late summer-early autumn. Spawning activity, as indicated by the incidence of spent females, began early in spring and ended in early autumn while water temperatures exceeded approximately 22�C. Nevertheless, ovary condition was apparently held constant during the colder non-spawning half of the year. Ovary condition was not correlated with either ovary coloui or crab size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 0 publications
2
23
2
3
Order By: Relevance
“…It was also the fishermen's experience that catches generally increased under conditions of high salinity and turbid water. Moreover, confirming results from other studies showing that the development stage of crustacean species, including S. serrata and Ranina ranina influences the catchability (Heasman et al, 1985;Skinner and Hill, 1987), moulting mud crabs and berried females were rarely captured in baited commercial crab traps. Temporal variance in catchability violates the assumption of constant catchability inherent in the nonlinear regression model.…”
Section: Discussionsupporting
confidence: 91%
“…It was also the fishermen's experience that catches generally increased under conditions of high salinity and turbid water. Moreover, confirming results from other studies showing that the development stage of crustacean species, including S. serrata and Ranina ranina influences the catchability (Heasman et al, 1985;Skinner and Hill, 1987), moulting mud crabs and berried females were rarely captured in baited commercial crab traps. Temporal variance in catchability violates the assumption of constant catchability inherent in the nonlinear regression model.…”
Section: Discussionsupporting
confidence: 91%
“…These conditions seemed to be ideal for successful incubation and larval development. Haesman et al (1985) while presenting a review of general trends of spawning activity of S. serrata has concluded that the length of the spawning period increases with the decreasing latitude. One of the reasons accounted was the availability of food in differential amounts in different seasons.…”
Section: Breedingmentioning
confidence: 99%
“…This view has been strengthened with high sex-ratio (males/females) during the peak breeding season. Secondly ovigerous females, if any, may not have been accessible for 'long lines' a major gear employed in backwaters, for catching S. serrata, by the simple fact that the intensity of feeding in crabs decline during berried state (Edwards 1979;Haesman et al 1985). Thirdly it could also be due to timidity or protective behaviour towards the eggs.…”
Section: Breedingmentioning
confidence: 99%
“…Scylla serrata is a large portunid crab that can reach a maximum carapace width (CW ) well in excess of 200 mm over the course of a 3-to 4-yr life span (Perrine 1978, Heasman 1980, Robertson 1996. Female S. serrata mature at between 80 and 120 mm CW (Hill 1975, Heasman et al 1985, Prasad et al 1990, Robertson and Kruger 1994; see also citations in Perrine 1978). Male S. serrata mature physiologically at 90-110 mm CW but may not be large enough to compete suc-cessfully for mates until achieving fully adult morphology (e.g., large claws) upon reaching carapace widths of 140-160 mm (Perrine 1978, Heasman et al 1985, Knuckley 1999.…”
mentioning
confidence: 99%